SISTEM HACCP KE DALAM SISTEM MANAJEMEN KEAMANAN PANGAN ISO 22000:2009 (STUDI KASUS DI PT INDOKOM SAMUDRA PERSADA) [The Merger of Quality Assurance System ISO 9001:2008 and HACCP system into Food Safety Management SystemISO 22000:2009 (Case Study at Indoko - Novri Ilmiawan; Sussi Astuti; Otik Nawansih (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The object of this research was to merge the application of HACCP system and ISO 9001:2008 in ISP company into ISO 22000:2009. The  research method used was case study method. The study was conducted on three stages. The first was the arrangement gap analysis conducted by comparing the conditions of the company with ISO 22000:2009 standards. The second was by observing sanitation and pre requisite programs. The third was by observing traceability system. The data in this research were reported descriptively, consisted of ISO 9001:2008 and HACCP application in the company and the gaps of principles in ISO 22000:2009 toward ISO 9001:2008 and HACCP. The result showed that ISP company has applied 12 steps which covered in HACCP system, and also the ISO 9001 system were appropriate with ISO 9001:2008 standards in every clauses. Pre requisite program (GMP and SSOP) have been effectively applied. GMP in ISP company is categorized on the first spot (excellent). The eight keys of SSOP have been fulfilled. ISP company has been fulfilling 54 from 57 (94.74%) criteria in ISO 22000:2009 standards, yet there still several things needed to be improved, which are the quality manual content  and HACCP table plan and its monitoring. The  traceability system has been applied well in ISP .   Key words : HACCP, ISO 9001, ISO 22000, GMP, SSOP.